Outcomes of solid organ transplant recipients with invasive aspergillosis and other mold infections. Issue 1 (6th November 2019) - Farges, Cédric; Cointault, Olivier; Murris, Marlène; Lavayssiere, Laurence; Lakhdar‐Ghazal, Shérazade; Del Bello, Arnaud; Hebral, Anne‐Laure; Esposito, Laure; Nogier, Marie‐Béatrice; Sallusto, Federico; Iriart, Xavier; Charpentier, Elena; et al.
Abstract: Objectives: To characterize the clinical presentation and outcomes of invasive mold infections (IMI) in solid organ transplant (SOT) recipients. Methods: Inclusion of all SOT recipients with IMI diagnosed between 2008 and 2016 at a referral center for SOT. Univariable analyses identified factors associated with death at one year, and logistic regression models retained independent predictors. Results: Of the 1739 patients that received a SOT during this period, 68 developed IMI (invasive aspergillosis [IA] in 58). Cumulative incidence of IMI at 1 year ranged from 1.2% to 18.8% (kidney and heart transplantation, respectively). At baseline, compared with other IMI, the need for vasoactive drugs was more frequent in patients with IA. During follow‐up, 35 patients (51%) were admitted to the ICU and required mechanical ventilation (n = 27), vasoactive drugs (n = 31), or renal replacement therapy (n = 31). The need for vasoactive drugs (OR 7.34; P = .003) and a positive direct examination (OR 10.1; P = .004) were independently associated with the risk of death at 1 year in patients with IA (n = 33; 57%) Conclusions: Characteristics of IMI at presentation varied according to the underlying transplanted organ and the mold species. Following IA, one‐year mortality may be predicted by the need for hemodynamic support and initial fungal load.